2009
DOI: 10.1371/journal.pone.0006405
|View full text |Cite|
|
Sign up to set email alerts
|

Inheritance of Acquired Behaviour Adaptations and Brain Gene Expression in Chickens

Abstract: BackgroundEnvironmental challenges may affect both the exposed individuals and their offspring. We investigated possible adaptive aspects of such cross-generation transmissions, and hypothesized that chronic unpredictable food access would cause chickens to show a more conservative feeding strategy and to be more dominant, and that these adaptations would be transmitted to the offspring.Methodology/Principal FindingsParents were raised in an unpredictable (UL) or in predictable diurnal light rhythm (PL, 12∶12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 41 publications
2
71
0
Order By: Relevance
“…In a number of experiments, we have exposed chickens to stress at different time periods during their lives (Goerlich et al, 2012;Lindqvist et al, 2007;Nätt et al, 2009). Generally, this caused permanent changes in both spatial and associative learning, as well as in foraging patterns and social dominance.…”
Section: Stress and Fear -Central Components Of Domesticationmentioning
confidence: 99%
“…In a number of experiments, we have exposed chickens to stress at different time periods during their lives (Goerlich et al, 2012;Lindqvist et al, 2007;Nätt et al, 2009). Generally, this caused permanent changes in both spatial and associative learning, as well as in foraging patterns and social dominance.…”
Section: Stress and Fear -Central Components Of Domesticationmentioning
confidence: 99%
“…Another key step will be to identify these epigenetic marks and quantify their inheritance. Indeed, a pioneer study revealed the inheritance of acquired behavior adaptation to unpredictable food access in chickens that could be because of variations in chromatine structure (Nätt et al, 2009).…”
Section: Exploiting Animal Adaptive Capacitiesmentioning
confidence: 99%
“…Some acute events, in addition to physical restraint, have been shown to induce a stress response in chickens, for example heat stress [27][28][29] and unpredictable light regimes [30]. Restraint stress however is a well-established method for triggering a stress response in chickens (see for example [29,31,32] ) where also the HPA-axis recovery has been investigated [31].…”
Section: Introductionmentioning
confidence: 99%